Laser Soldering of Cartilage Graft Interposed Into a Tracheal Incision in a Porcine Model. (12th September 2018) - Yafit, Daniel; Basov, Svetlana; Katzir, Abraham; Fliss, Dan; DeRowe, Ari
Abstract : Objectives/Hypothesis: Investigate the feasibility of soldering a free cartilage graft into a tracheal defect by laser heating and assessing the resulting burst pressure and thermal damage to the cartilage. Study Design: Animal study. Methods: A 20 × 8 mm defect was created in fresh cadaveric pig tracheas, a cartilage graft of the same size was harvested from the thyroid ala cartilage, and the graft was fitted into the defect. The soldering process involved covering the edges with liquid albumin and using a fiber‐laser system for heating the edges to temperature T under temperature control. This was done for groups of grafts at various temperatures T = 60°C to 90°C. The tracheas were sealed, for each group the burst pressure was measured, and a histologic examination of the soldered incisions was performed. Results: The burst pressures were in the range of 66 to 409 mm Hg. The median burst pressure was 78, 157, 231, and 146 mm Hg, respectively, for T = 60°C, 70°C, 80°C, and 90°C. Statistical analysis revealed significant differences in burst pressures between the T = 60°C group and the T = 80°C and T = 90°C groups ( P < .05). The highest burst pressure was measured in the T = 80°C group. Histologic examination revealed no thermal damage to the cartilage at this temperature. Conclusions: Performing a sutureless laser soldering of a free cartilage graft to a tracheal defect, achieving an immediate watertight bond, is feasible. At T = 80°C the highest burst pressures were achieved. No histologic damage was observed. In vivo studies are needed before implementation of this technique in laryngotracheopasty. Level of Evidence: NA Laryngoscope, 129:58–62, 2019